The Relationship between Knowing and Liking for 91 Urban Animal Species among Students - Fabio S. T. Sweet; Peter Noack; Thomas E. Hauck; Wolfgang W. Weisser (Animals, 2023)
While there is growing consensus that nature should be promoted in cities, it is less clear what kind of nature this should be. One hypothesis is that humans show greater liking for those parts of nature that they know better. Using questionnaires, we studied the familiarity of 475 students with 91 urban animal species and the relationship between familiarity and attitudes towards the species. Students declared that they were familiar with most animals, but not all animals were equally liked. Better-known species were not generally the better-liked ones. The more familiar animal species were the more extreme attitudes became towards them, both positively and negatively. Our research shows that familiarity and attitude are not two sides of the same coin. It also emphasizes that there are parts of nature that are not liked by many humans and that this dislike is not necessarily correlated with insufficient knowledge. Detailed studies of what components of nature humans like and reasons underlying this are necessary to successfully increase nature in cities.